Corporate Strategies to Defend Social Irresponsibility: A Typology of Symbolic and Substantive Tactics - Reuter, Emmanuelle; Ueberbacher, Florian (Cham: Springer, 2019)
Social responsibility issues arise as stakeholders perceive and articulate a mismatch between the organization’s current way of functioning and the existing expectations of what socially responsible or normatively appropriate behavior would be. While such issues may exist in any organization, when they become salient, they have the potential to have fundamentally negative consequences for organizations, for instance, declining sales, increased costs of capital, negative reputation, loss of partner support, etc. Much prior research uncovered how organizations manage the saliency of social responsibility issues in social responsibility–congruent ways, that is, by creating positive externalities for society. In this chapter, we address how organizations act to manipulate the saliency of stakeholders’ perceptions by remaining “socially irresponsible.” We argue that organizations may skillfully use different types of impression management strategies—proactive discursive defense, proactive material defense, reactive discursive defense, reactive material defense—to avert the salience of social responsibility issues. These strategies are illustrated with case examples.
Keywords: corporate social responsibility; impression management; symbolic compliance; substantive compliance